Short term analysis of total hip replacement done with constrained acetabular component - functional and radiological outcome - Vanchi, Pravin K.; Veeraraghavan, Raghav Ravi; Vasudevan, Saravanan; Murugesan, Mohan Kumar (International Journal of Research in Orthopaedics, 2022)
Background: Dislocation remains at the forefront of complications after primary total hip arthroplasty (THA). In our study, we talk about the use of constrained liners and its outcomes in an unstable hip. Methods: The total number of patients included in the study was 15. The total number of hips in the study were 15. The age group of the patients varied between 51 years and 89 years with mean age group of 73 years. The most common indication in our study was dislocation contributing 60% (n=9) of the hips. Results: The post-operative mean Harris hip score (HHS) at immediate post-operative was 67.6. There was a gradual improvement in the HHS through 6 months (77.6), one year (83.3), two years (86.7) and 3 years (90.33). There were no cases with post-operative septic or aseptic loosening in the radiological analysis. The mean cup inclination was 34.3. Out of the 13 hips, in eight hips the femoral stem was in varus. Five hips had a centrally placed femoral stem. Stability management in THA have seen the component design take centre stage, primarily with the use of larger diameter femoral heads and the rise in popularity of constrained acetabular liners (CAL). Several authors have done studies which talk about the stability of this implant design and the reliability of this implant in unstable hips and in hips where instability was expected. Conclusions: In our study, proximal femur tumours, dislocated total hips, abductor insufficiencies and aseptic loosening all showed good results.